2021
DOI: 10.1111/ans.16941
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty on clinical outcomes in colorectal cancer surgery: a systematic literature review

Abstract: Background The majority of colorectal cancer is diagnosed in people aged >65 years, yet the elderly are less likely to undergo curative surgery. Chronological age is poorly correlated with post‐operative outcomes and is not an acceptable measure of risk. Conversely, frailty is a strong predictor of poor post‐operative outcomes and presents an opportunity for optimisation. This systematic review aims to assess the evidence between frailty and outcomes in patients of all ages undergoing colorectal cancer resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…Moreover, age did not present any association with surgical site infection, anastomotic leak, or with reoperation rate. These findings are consistent with those obtained from other large series, where age was not predictive of in-hospital complications or mortality, suggesting that other conditions may impact more significantly in surgical outcomes [ 8 , 12 , 14 , 19 , 20 , 25 ]. Therefore, it would be more appropriate to consider a frailty index rather than age in preoperative decision-making.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, age did not present any association with surgical site infection, anastomotic leak, or with reoperation rate. These findings are consistent with those obtained from other large series, where age was not predictive of in-hospital complications or mortality, suggesting that other conditions may impact more significantly in surgical outcomes [ 8 , 12 , 14 , 19 , 20 , 25 ]. Therefore, it would be more appropriate to consider a frailty index rather than age in preoperative decision-making.…”
Section: Discussionsupporting
confidence: 91%
“…Several factors have been identified that could increase the risk of postoperative adverse events in older patients: comorbidities, male sex, tumor location, operation time, open surgery, and emergent surgery. Interestingly, age has not appeared as a factor increasing postoperative complications or mortality rate [12,14,[17][18][19][20][21]. Some authors have reported comorbidities as the strongest predictors of postoperative complications in aged patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, age did not present any association with surgical site infection, anastomotic leak or with reoperation rate. These ndings are consistent with those obtained from other large series, where age was not predictive of in-hospital complications or mortality, suggesting that other conditions may impact more signi cantly in surgical outcomes [8,12,14,19,20,23].…”
Section: Discussionsupporting
confidence: 90%
“…Several factors have been identi ed that could increase the risk of postoperative adverse events in older patients: comorbidities, male sex, tumor location, operation time, open surgery and emergent surgery. Interestingly, age has not appeared as a factor increasing postoperative complications or mortality rate [12,14,[17][18][19][20][21]. Some authors have reported comorbidities as the strongest predictors of postoperative complications in aged patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, older patients are also a heterogeneous group with regard to comorbidities, physical capabilities and the presence of geriatric impairments such as decreased mobility, malnutrition, polypharmacy and cognitive problems. Several studies have found an association between these geriatric impairments and adverse postoperative outcomes in older patients with CRC [4][5][6][7]. Adequate risk stratification in older patients is required to support informed decision-making and to adjust perioperative strategies such as the implementation of prehabilitation (preoperative physical optimization) programs.…”
Section: Introductionmentioning
confidence: 99%